Assessment of the Housing Market Development Level as a Condition for Ensuring Economic Security of Households - Egor GOLOVANOV; Olga RYAZANTSEVA; Anna CHEREPANOVA; Marina BAZHANOVA (Communications of International Proceedings, 2020)
The article proves the necessity of carrying out an estimation of housing market development level as important condition for maintenance of economic safety of households. The authors have defined the essence of the state of economic security of households in modern living conditions. The article highlights the most important spheres of vital activity of households and describes in more details risks and threats that directly or indirectly influence a condition of their economic security. It is emphasized that the housing sphere is one of the most important areas, as on the one hand it is the habitat of households, and on the other hand it has a direct impact on the state of their economic security. A group of quantitative and qualitative indicators has been proposed, which, according to the authors, will allow for more clear assessment of the housing market development level for the purpose of ensuring the economic security of households regardless of the territory of residence. The proposed methodology is based on the calculation of integral indicator on the basis of a set of indicators, grouped into four areas: housing, housing services, government support to households in the housing market, the assessment of household welfare. It is shown that the calculation of the integral indicator for assessing the housing market development level will rank regions based on the development of this market as a condition of economic security of households in each region. The developed method was tested on the example of territorial and administrative units within the Urals Federal District of Russia. The results of the study are of practical importance, as they provide an opportunity to rank the regions both in terms of their constituent areas and in terms of the complex integrated housing market development indicator. This will allow state and regional authorities to formulate more clearly the tasks of improving the current housing policy, which will undoubtedly allow households to increase their economic security by minimizing the relevant risks and threats to their life activities.
Keywords: Households; Economic Security of Households; Threats and Risks to The Economic Security of Households; Housing Market; Housing Services; Integral Assessment; Method of Analysis of Hierarchies; The Housing Market Development Level.